Anti-Inflammatory of Papaya Leaf Extract (Carica Papaya L) Towards Membrane Stabilization of Red Blood Cells - Laila Kamilla; Sri Tumpuk; Maulidiyah Salim (poltekkes kemenkes mataram, 2021)
Traditional medical plants are known to society long ago. Apart from easily obtained and inexpensive, it can cure diseases with few side effects than modern medicine. Papaya leaves were used not only because of contained various chemical compounds with pharmacological effects but also alkaloids, flavonoids, saponins, and tannins compounds indicated as anti-inflammatory. This study applied a quasi-experimental design to test the papaya leaves anti-inflammatory activity. The red blood cell stabilization method was employed because analogous to the lysosomal membrane affected the inflammatory process. Purposive sampling was used, creating papaya leaves extract of 50 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, and 800 ppm concentration, made 24 total samples by four times replication. Based on the red blood cell lysis inhibition, the anti-inflammatory activity was measured and was compared with the positive control (diclofenac sodium). The papaya methanol extract result showed the highest anti-inflammatory activity at 800 ppm of 74.29%. The most effective concentration was at 200 ppm of 62.19%. Tukey's test showed p1.000 ≥ 0.05, suggesting H0 was accepted. There was no difference between the anti-inflammatory activity of papaya leaf methanol extract and diclofenac sodium showing stabilization of red blood cell membranes, indicating papaya potentially as an anti-inflammatory.